Pelatihan CorelDraw Pada Santri Yayasan Yatim Piatu dan Dhuafa Al-Ikhlas Bekasi - Khaerudin, Muhammad; Rasim, Rasim (Journal Of Computer Science Contributions (JUCOSCO), 2022)
The pandemic condition opens up opportunities for teenagers to do business. In this condition, it is expected that teenagers can use their time positively and productively. Mental readiness and skills need to be prepared before someone enters the world of work. Meanwhile applications in the field of information technology have a major impact in various fields of life, one of which is in the creative industries such as advertising, billboards, graphic design and digital image processing. One of the support skills for the younger generation. The method of community service carried out by a team of Bhayangkara Jakarta Raya University lecturers this time is in the form of graphic design skills training using computers and using CorelDraw and Photoshop software. This activity aims to improve the knowledge and skills of youth in improving the quality of their ability to create attractive graphic designs so that participants can compete to meet the demand for job opportunities and also towards entrepreneurship. Mareri given to participants include making and completing product designs for advertising or printing needs. The results of the graphic design skills training activity show that participants can design logos, business cards, invitations, flyers, banners, banners and other forms of advertising.